Fluid properties impact on energy separation in Ranque–Hilsch vortex tube - Al Saghir, Ahmad Mohammad (2022)
This paper examines the energy separation in vortex tubes which is a passive device that can split a pressurized room temperature gas stream to hot and cold streams. The paper employs numerical simulations to investigate the impact of various working fluids such as helium, air, oxygen, nitrogen, and carbon dioxide on the energy separation in the vortex tube, using the SST k− turbulence model with viscous heating. A three-dimensional numerical investigation is sued to examine the effect of a single fluid property on vortex tube performance, while keeping the rest of the fluid properties unchanged, which is impossible to achieve via experimental study. The numerical investigation examines the influence of molecular weight, heat capacity, thermal conductivity, and dynamic viscosity on energy separation. The results show that energy separation performance improves with lower molecular weight and heat capacity, and higher dynamic viscosity of the working fluids, while no impact of the thermal conductivity is observed. Out of five gases tested in this study, helium has yielded the maximum temperature separation, while carbon dioxide has yielded the lowest performance. Results show that viscous dissipation contributes to the temperature separation in vortex tube.